Identification of factors related to attempted suicide in children and adolescents from the application of the nursing care process (Colombia Medica, 2024)
Objective: To identify the factors related to attempted suicide in a group of children and adolescents hospitalized in the Mental Health Unit at the «Evaristo Garcia» Hospital Universitario del Valle and in their family groups.Materials and methods: Exploratory-descriptive research. An assessment was used according to Marjory Gordon's functional health patterns. Sixteen minors and 14 of their parents or legal guardians were surveyed.Findings: Protective factors were identified, especially in values and beliefs and role-relationship patterns, and risk factors in patterns of the health management perception and tolerance-confrontation to stress. In addition, changes in patterns were observed: metabolic nutritional, activity-exercise, and sleep-rest.Conclusion: The risk factors identified, as well as the presence of a triggering event and the availability of a suicide method increase the risk suicide attempt in children and adolescents. The application of the nursing care process facilitated obtaining information and identifying risk factors related to attempted suicide becoming a tool of the discipline, which contributes to systematization and nursing research.